Revestimentos de quitosana incorporados de óleos essenciais de Mentha piperita L. e M. x villosa Huds para o controle de antracnose e qualidade pós-colheita em mamão (Carica papaya L.) - Braga, Selma dos Passos (2020)
Postharvest losses of fruits represent a global concern, such as those occurring in papaya (Carica papaya L.), which is known as one of the most important tropical fruits with remarkable economic importance, but very susceptible to the development of fungal diseases, especially,anthrachnose caused by Colletotrichum species. Control of anthracnose in papaya has been reached with the application of synthetic fungicides, which can cause damage to the environment and consumer esides inducing resistant fungal strains occurrence. In this context, this study aimed to evaluate the efficacy of coatings formulated with chitosan (Chi) and essential oils from Mentha piperita L. (MPEO) or M. villosa Huds (MVEO) to control the development of anthracnose caused by C. gloeosporioides and C. brevisporum isolates in papaya. To reach these objectives, in vitro tests were conducted to evaluate the fungal mycelial growth and type of interaction between Chi and MVEO or MPEO, as well as in situ tests to evaluate the efficacy of the coatings to inhibit the development of anthrachnose lesions in papaya artifically infected with fungal isolates during storage (25 °C, 10 days) .In addition, the physicochemical characteristics of coatings with FTIR, TGA and DSC analysis were evaluated, as well as the surface rugosity and the effects of the application of these coatings on physicochemical and sensory parameters related to the postharvest quality of papaya. Chi (2.5; 5; 7.5 and 10 mg/mL), MVEO and MPEO (0.15; 0.3, 0.6 and 1.25 L/mL) inhibited the growth of C. gloeosporioides and C. brevisporum isolates in vitro, and combinations of Chi (5 or 7.5 mg/mL) and MVEO or MPEO (0.15; 0.3; 0.6 or 1.25 mL/mL) had additive or synergistic interactions. Fruits coated with combinations of Chi (5 mg/mL) and MVEO or MPEO (0.3; 0.6 or 1.25 L/mL) showed a reduction in the development of anthracnose lesions during storage and these effects were similar to or higher than those caused by a commercial synthetic fungicide formulation (trifloroxistrobin + tebuconazole). The results of the characterization of the coatings formulated with Chi (5 mg/mL) and MVEO or MPEO (0.6 or 1.2 L/mL) showed an increase in intensity of FTIR bands, suggesting a possible interaction between components used in their formulation. MVEO and MPEO affected the coating thermal stability positively. Surface roughness analysis showed that the formulated coatings (with Chi and MVEO or MPEO) had homogeneous surfaces, being capable of forming a physical barrier on fruit. Fruits coated with Chi (5 mg/mL) and MVEO or MPEO (0.6 or 1.2 L/mL) had a delay in the evolution of some physico-chemical parameters related to the advance in the maturation process, besides not affecting negatively most of their sensory parameters during storage (12 ± 0.5 °C). These results suggest that the application of coatings formulated with selected combinations of Chi and MVEO or MPEO could be a strategy to cause postharvest control of anthracnose in papaya, without affecting negatively aspects related to fruit overall quality.